Stable efficient solid-state supercapacitors and dye-sensitized solar cells using ionic liquid-doped solid biopolymer electrolyte - Konwar, Subhrajit; Gultekin, Sirin Siyahjani; Gultekin, Burak; Kumar, Sushant; Punetha, Vinay Deep; Yahya, Muhd Zu Azhan; Diantoro, Markus; Abdul Latif, Famiza; Mohd Noor, Ikhwan Syafiq; Singh, Pramod K. (American Chemical Society, 2024)
As synthetic and nonbiodegradable compounds are becoming a great challenge for the environment, developing polymer electrolytes using naturally occurring biodegradable polymers has drawn considerable research interest to replace traditional aqueous electrolytes and synthetic polymer-based polymer electrolytes. This study shows the development of a highly conducting ionic liquid (1-hexyl-3-methylimidazolium iodide)-doped corn starch-based polymer electrolyte. A simple solution cast method is used to prepare biopolymer-based polymer electrolytes and characterized using different electrical, structural, and photoelectrochemical studies. Prepared polymer electrolytes are optimized based on ionic conductivity, which shows an ionic conductivity as high as 1.90 × 10-3 S/cm. Fourier transform infrared spectroscopy (FTIR) confirms the complexation and composite nature, while X-ray diffraction (XRD) and polarized optical microscopy (POM) affirm the reduction of crystallinity in biopolymer electrolytes after doping with ionic liquid (IL). Thermal and photoelectrochemical studies further affirm that synthesized material is well stable above 200 °C and shows a wide electrochemical window of 3.91 V. The ionic transference number measurement (tion) confirms the predominance of ionic charge carriers in the present system. An electric double-layer capacitor (EDLC) and a dye-sensitized solar cell (DSSC) were fabricated by using the highest conducting corn starch polymer electrolyte. The fabricated EDLC and DSSC delivered an average specific capacitance of 130 F/g and an efficiency of 1.73% in one sun condition, respectively.